The battle for home :bthe vision of a young architect in Syria - Al-Sabouni, Marwa (Thames & Hudson Ltd., 2016)
Drawing on the author's personal experience of living and working as an architect in Syria, this book offers an eyewitness perspective on the country's bitter conflict through the lens of architecture, showing how the built environment offers a mirror to the community that inhabits it